Acute upper limb ischemia: 30 years’ experience - M. V. Mel'nikov; A. V. Sotnikov; P. A. Susla; G. G. Papava (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE of the study was to assess the current trends in the surgery of acute upper limb ischemia (AULI). MATERIAL AND METHODS. We performed the comparative analysis of clinical data and treatment results of 261 patients with AULI urgently treated between 2008 and 2018 years (main group) and 162 patients with AULI treated between 1975 and 1985 years (control group). RESULTS. For the past 30 years, there were the growing rate of AULI. In 92.7 % of cases, the main cause of AULI was embolism. The main disease leading to embolism became atrial fibrillation in 80.8 % of cases. For the past decades, there was a significant improvement of treatment results in patients with AULI: complete extremity blood flow supply was achieved in 95 % in main group vs 90.5 % in control group (p<0.05); postoperative mortality rate significantly decreased to 3.5 vs 8.8 % respectively (p<0.05). CONCLUSION. AULI continued to remain the actuality in modern vascular surgery.